New Purcell Documents from the Court of King's Bench. Issue 1 (2016) - Duncan, Cheryll
Abstract : Two legal documents recently discovered among The National Archives at Kew in London provide new information about Henry Purcell's final years. The only known instances of the composer's involvement with the law, these rare archival finds shed light on his familial relations and financial circumstances at that point in his career when he was turning his attention to the London stage. The first case involves Purcell's sister-in-law Amy Howlett, who owed him £40; and the second concerns his unpaid bill at an exclusive West End retailer's. The new material confirms beyond doubt the identity of Purcell's in-laws, and shows that he was not just short of money in the 1690s, but that he was actually in debt at the time of his death. Other areas of enquiry include the élite social milieu in which the Purcells increasingly moved, and their possible place of residence in 1691–3. These aspects are discussed in relation to Purcell's enhanced public profile at that time, and within the wider context of the culture of consumption and credit in late seventeenth-century England. The two lawsuits are transcribed and translated in full, and their legal implications explicated.